A Good Performance OTP Encryption Image based on DCT-DWT Steganography - Wellia Shinta Sari; Eko Hari Rachmawanto; De Rosal Ignatius Moses Setiadi; Christy Atika Sari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The security aspect is very important in data transmission. One way to secure data is with steganography and cryptography. Surely research on this should continue to be developed to improve security. In this paper, we proposed a combination of steganographic and cryptographic algorithms for double protection during data transmission. The selected steganographic algorithm is the use of a combination of DCT and DWT domain transformations. Because the Imperceptibility aspect is a very important aspect of steganographic techniques, this aspect needs to be greatly improved. In the proposed method of DCT transformation first, proceed with DWT transformation. From the experimental results obtained better imperceptibility quality, compared with existing methods. To add OTP message security applied algorithm to encrypt the message image, before it is inserted. This is evidenced by experiments conducted on 20 grayscale images measuring 512x512 with performance tests using MSE, PSNR, and NC. Experimental results prove that DCT-DWT-OTP generates PNSR more than 50 dB, and NC of all images is 1.